Kebijakan Vasektomi Sebagai Instrumen Perencanaan Keluarga Perspektif Maqashid Al-Usrah Jamaluddin Athiyyah - Nabiela Rafa Callysta; Nabila Salma Amaliya; Firmansyah Firmansyah; Suwandi Suwandi; Saifullah Saifullah (Hukum Islam, 2026)
This study aims to analyze vasectomy policy as a family planning instrument through the lens of Maqashid al-Usrah formulated by Jamaluddin Athiyyah. Using a qualitative method and a normative-juridical approach, the study examines legal regulations, religious fatwas, Islamic literature, and relevant medical data. The findings reveal that although vasectomy is a permanent contraceptive method, it does not inherently contradict Islamic principles if performed voluntarily, based on mutual consent, and not intended as irreversible sterilization. From the Maqashid al-Usrah framework, vasectomy can represent: (1) Tanzhim al-‘Alaqah baina al-Jinsayn justice and shared responsibility between spouses; (2) Hifz an-Nasl responsible limitation to protect the quality of offspring; (3) Tahqiq as-Sakan wa al-Mawaddah wa ar-Rahmah preservation of emotional harmony and spousal compassion through health-oriented decisions; (4) Tanzhim al-Janib al-Mu’assis lil Usrah collective and ethical family decision-making; and (5) Tanzhim al-Mal lil Usrah financial stability through proportional family planning. This study argues that a contextual maqashid approach allows vasectomy to be understood not as prohibited sterilization, but as a preventive measure for long-term family welfare. The implication of this research underscores the urgency of formulating family policies that are just, Sharia-compliant, and uphold the reproductive rights of both partners